Standard Levels of Modern Administration for the Iraqi Central Olympic Committee’s Olympic Federations - Sami, Faris; Mohammed, Hussein (Journal of Physical Education, 2017)
The problem of the research lies in the lack of standard levels for modern administration as a guide for evaluating weaknesses and strengths as well as finding solutions. The aim of the research lies in identifying standard levels for modern administration in Iraqi central Olympic committee and international federations. The subjects were (24) Olympic committee’ federations. All procedures were standardized to fit our modern administration work. The data was collected and treated using proper statistical operations. The researcher concluded standard levels for modern administration in international federation of the Iraqi Olympic committee, in addition to that he concluded that most administrations levels ranged within four levels (good, fair, accepted, weak) as well as administrators in these federations lack active scientific administration and understanding of most administrative concepts